Brine Shrimp Toxicity of Essential Oils from Musa spp. - Mohd Alhafiizh, Zailani; Abdul Razzak Fikri, Sharkawi (UNIMAS Publisher, 2019)
Essential oils of seven Musa spp.’s fruits namely, Musa acuminata colla ‘gros michel’ (PE), Musa acuminata colla ‘lakatan’ (PB), Musa acuminata colla ‘sucrier’ (PM), Musa acuminata × balbisiana ‘horn plantain’ (PT), Musa acuminata × balbisiana colla ‘saba’ (PN), Musa acuminata colla 'inarnibal' (PO) and Musa acuminata colla ‘red’ (PJ) were extracted by hydrodistillation method using Clevenger apparatus. The essential oils were analysed using GC-FID and identified using Kovat Indeces compared with published information. PE gave the highest yields of oils compared to the other species with yield of 0.43% and 0.28% for its peels and flesh, respectively. The most abundant groups present in most of the essential oils are ester and alcohol groups. The brine shrimp toxicity of PT, PM, PN and PO essential oils were tested and showed toxicity against brine shrimp in dose dependent manner. It can be concluded that the essential oils showed some biological activities which may be a potent medicine in curing tumor. This study implies that the presence of ester and alcohol groups are a good marker for the biological activities of plants. Further studies should focus on the potential of the essential oils of Musa spp. as an antitumor medicine